The Effects Of Alkaline Earth Metals In Nimo-x (X = Mg, Ca, Sr, Ba) Catalysts On The Characteristics Of Carbon Nanotubes Derived From Plastics Pyrolysis - Lim, Xiu Xian (2024)
The increased usage of face masks has spurred environmental concerns, necessitating effective waste management strategies. One effective approach is to upcycle face mask plastic waste into carbon nanotubes (CNTs) through catalytic pyrolysis. Typically, the plastic-derived hydrocarbons, at high temperatures, contact the metal catalysts, allowing the supersaturation state of metal carbide and the formation of CNTs. To date, most research only reports the alkali earth metal elements as thermal supporting material without clarifying their impacts on metal activity in CNTs synthesis, limiting the manipulation of CNTs characteristic for applications. As such, this study aims to investigate the impacts of alkali earth metals towards the CNTs synthesis from the perspective of surface Ni activity, surface characteristic, and metal phases loading. This study utilized the NiMo-Ca-n (n = 0, 7, 15, and 32) and NiMo-X (X = Mg, Ca, Sr, Ba) catalysts prepared via solution combustion synthesis for one-pot synthesis of CNTs from face masks. In the first part of the study, it was discovered that at optimum Ca loading (n = 15), the presence of CaMoO4 (14.1 wt.%) and CaCO3 (13.4 wt.%) phases yielded longer CNTs with a carbon yield of 6.4 wt.% instead of carbon nanospheres and carbon fragments. Further increase in Ca loading with a high CaCO3 fraction (29.7 wt.%) would lower its carbon yield to 5.4 wt.% with short CNTs appearance. In the second part of the study, it was found that weaker Ni-X interaction moving down the Group 2 elements within NiMo-X jeopardizes the formation of CNTs, resulting in carbon flakes instead, especially from NiMo-Ba with a carbon yield at 3.1 wt.%.